ANALYSIS OF STIE GANESHA CAMPUS FACILITY NEEDS BASED ON THE VIEWS OF STUDENTS AND LECTURERS - Agya Mutia Alifta; Aep Saefullah; Ahmad Fadli; Elvira Sitna Hajar; Fisy Amalia; Ika Agustina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to evaluate the deficiencies in the learning of accounting software at STIE Ganesha. This study will concentrate on factors that potentially hinder the integration of accounting software into the college curriculum. This research started in October 2024. Accounting students at STIE Ganesha are the research subjects. Qualitative research was conducted and data was collected through in-depth interviews. The results showed that learning accounting software has several problems. One of them is the lack of supporting resources and lack of technological infrastructure. In addition, students face difficulties in understanding and accessing accounting software required to meet the needs of the working world. To produce more efficient accounting software learning, this research emphasizes increasing resource capacity and improving supporting infrastructure. This research is expected to help STIE Ganesha develop methods to improve software-based accounting learning.